Arabidopsis Squalene Epoxidase 3 (SQE3) Complements SQE1 and Is Important for Embryo Development and Bulk Squalene Epoxidase Activity - Laranjeira, Sara; Amorim-Silva, Vitor; Esteban del Valle, Alicia; Arró, Montserrat; Ferrer, Albert; Tavares, Rui M.; Botella-Mesa, Miguel Ángel; Rosado, Abel; Azevedo, Herlânder (ScienceDirect, 2015)
The existence of multigenic families in the mevalonate pathway suggests divergent functional roles for pathway components involved in the biosynthesis of plant sterols. Squalene epoxidases (SQEs) are key components of this pathway, and Squalene Epoxidase 1 (SQE1) has been identified as a fundamental enzyme in this biosynthetic step. In the present work, we extended the characterization of the remaining SQE family members, phylogenetically resolving between true SQEs and a subfamily of SQE-like proteins that is exclusive to Brassicaceae. Functional characterization of true SQE family members, Squalene Epoxidase 2 (SQE2) and Squalene Epoxidase 3 (SQE3), indicates that SQE3, but not SQE2, contributes to the bulk SQE activity in Arabidopsis, with sqe3-1 mutants accumulating squalene and displaying sensitivity to terbinafine. We genetically demonstrated that SQE3 seems to play a particularly significant role in embryo development. Also, SQE1 and SQE3 both localize in the endoplasmic reticulum, and SQE3 can functionally complement SQE1. Thus, SQE1 and SQE3 seem to be two functionally unequal redundant genes in the promotion of plant SQE activity in Arabidopsis.
Keywords: Esteroles; Arabidopsis; embryo development; MVA pathway; squalene epoxidase; sterol biosynthesis